The Influence of Macroeconomic Factors on Credit Risk of Banks in Indonesia using ARDL Model - Lexy Janzen Sinay; Esther Kembauw (Pattimura International Journal of Mathematics (PIJMath), 2023)
One of the efforts to maintain economic stability during the Covid-19 pandemic is to reduce the risk of in the banking sector. One of the risks in the banking sector that must be anticipated is credit risk. Non-Performing Loan (NPL) is one of the indicators used to detect credit risk. There are various factors that can affect credit risk, both from internal and external banking. One of the external factors that can affect NPL is macroeconomic conditions. This study aims to identify macroeconomic factors that affect banking NPLs in Indonesia using the autoregressive distributed lag (ARDL) model. The data used is time series data from January 2015 – August 2020, which period describes the condition of the Indonesian economy before and during the Covid-19 pandemic. The data consists of six variables, namely the NPL ratio of commercial banks and macroeconomic factors in Indonesia such as gross domestic product (GDP), inflation rate, USD-IDR exchange rate, benchmark interest rates [BI 7-Day (Reverse) Repo Rate], and credit growth. The results of the data analysis show that the NPL ratio and macroeconomic variables are experiencing shocks due to the COVID-19 pandemic. The results of the ARDL model analysis show that these macroeconomic variables are able to explain the NPL of 66.61%